Puzzles of Capitalism and the World of Life - Belluzzo, Luiz Gonzaga (Cadernos do Desenvolvimento, 2023)
Special contribution by Professor Dr. Luiz Gonzaga Belluzzo to the dossier "Development, health and structural change: The Health Economic-Industrial Complex 4.0 in the context of Covid-19" in the journal Cadernos do Desenvolvimento, Rio de Janeiro, "Celso Furtado", v . 16, n. 28, p. 19-26, Jan.-Apr. 2021.